The Construction of Fathers New Masculinity in South Korea Variety Show Superman is Back - Iryanti, Muri (Humaniora, 2017)
This research focused on the construction of new masculinity in South Korea parenting and fatherhood at the variety showen titled “Superman is Back”. This variety show itself was a part of the existence of Korean popular culture that was also called Hallyu. Hallyu became the phenomenon that swept other popular culture which previously developed in some countries. Hallyu could shift the previous pop culture with the good strategy. The selection of this television show was intended to see how a television program constructed the kind of new masculinity of men, in this case, celebrity fathers that join the show. The qualitative method was employed in this research to find the gender issue and new masculinity discourse which was portrayed by the fathers. The result shows that “Superman is Back” tries to display the different masculinity that is constructed by the show and this is different from the traditional one. This is the alliance of men with new masculinity that is less oppressed women as embedded in the context of patriarchal culture. The portrayals of new masculinity can be seen in the way fathers do nurture, cook, change the baby’s diaper, dance practice, and play with their children. “Superman is Back” is an attempt to show father as nurturer and has the role in domestic tasks too.